PELATIHAN DASAR-DASAR FOTOGRAFI DAN EDITTING VIDEO UNTUK PROMOSI PRODUK BAGI PELAKU USAHA MIKRO DAN KECIL DI KOTA PONTIANAK - Krisiandy, Samuel Dendy; Yuardani, Ade M; Arief, Verdico Arief; Wahyuni, Endang; Sihombing, Grace Kelly H.P.; Saputra, Haris Mirza; Rachimoellah, Muhammad (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Becoming an entrepreneur in Indonesia is not only a professional choice, but also a force that drives the wheels of the country's economy. The use of online platforms by MSMEs in Indonesia is still relatively low, with only 8% utilizing this media in 2021. This training is designed to provide understanding and skills in creating and editing photography and marketing videos so that they can not only highlight the product image, but It also makes it easier for consumers to understand and be interested in the products offered through lecture methods and direct practice carried out by each participant. By carrying out training in photography and video editing techniques, knowledge and skills will certainly increase so that they can improve the visual quality of their products, which is very important in marketing in the digital era